2015
DOI: 10.1186/s13148-015-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb-mediated silencing in neuroendocrine prostate cancer

Abstract: BackgroundNeuroendocrine prostate cancer (NEPC) is a highly aggressive subtype of prostate cancer (PCa) for which the median survival remains less than a year. Current treatments are only palliative in nature, and the lack of suitable pre-clinical models has hampered previous efforts to develop novel therapeutic strategies. Addressing this need, we have recently established the first in vivo model of complete neuroendocrine transdifferentiation using patient-derived xenografts. Few genetic differences were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 72 publications
10
123
0
Order By: Relevance
“…This study also identified 185 PcG target genes that were significantly down-regulated indicating a relevant role of PcG complexes in NEPC. This 'neuroendocrine-associated repression signature' (NEARS) is associated with higher-grade neoplasms, metastatic progression, and poor outcome in multiple clinical datasets [26]. In line with this model, we also found that the chromatin modifier DEK is up-regulated in NEPC cells, and that targeting this gene reduces NEPC proliferation and migration [53].…”
Section: The Epigenetic/non-coding Interactome and Its Implication Insupporting
confidence: 65%
See 4 more Smart Citations
“…This study also identified 185 PcG target genes that were significantly down-regulated indicating a relevant role of PcG complexes in NEPC. This 'neuroendocrine-associated repression signature' (NEARS) is associated with higher-grade neoplasms, metastatic progression, and poor outcome in multiple clinical datasets [26]. In line with this model, we also found that the chromatin modifier DEK is up-regulated in NEPC cells, and that targeting this gene reduces NEPC proliferation and migration [53].…”
Section: The Epigenetic/non-coding Interactome and Its Implication Insupporting
confidence: 65%
“…To identify the mechanisms of NEPC initiation, we conducted transcriptomic and genomic analyses on our ADT-induced NEPC model (LTL-331R) and on its hormone-sensitive predecessor (LTL-331). We found that the two models share identical genetic profiles, suggesting that genetic alterations may not exclusively drive NEPC trans-differentiation [36].Interestingly, our analysis revealed that CBX2 and EZH2 (PcG members) were significantly up-regulated in NEPC pre-clinical models and clinical samples [26]. This study also identified 185 PcG target genes that were significantly down-regulated indicating a relevant role of PcG complexes in NEPC.…”
supporting
confidence: 58%
See 3 more Smart Citations